Consumer Behavior as a Symbolic Interaction in the Virtual Dimension - Sіusel, Yuliya (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
This article deals with the attempt to analyze consumer behavior in the modern virtual dimension. The main features of consumer behavior basing on the concept of symbolic interactionism are considered. The way how the global infrastructure of the Internet and commercialization of the Internet have led to changes in consumption patterns based on the principles of the network economy is analyzed. The changes of sign-symbolic relations in consumption that are the result of the forecasted development of electronic commerce are defined.